Pengaruh Arus Kas Operasi Dan Leverage Terhadap Return Saham Pada Perusahaan Idx 30 Yang Terdaftar di Bursa Efek Indonesia - Hendrick Sasimtan Putra; Anggraini Syahputri; Erna Ningsih Mokodongan; Debi Eka Putri; Ni Wayan Dian Irmayani (Strategic: Journal of Management Sciences, 2024)
Objective. The research is to understand how cash flow from operations and leverage affect the stock returns of companies registered in the IDX30 index during the period 2017-2021. Research Method. The study employs purposive sampling, appearing in a selection of 10 companies. The analytical approach includes classical assumption testing, analysis of multiple linear regression, correlation coefficient and determination, and also hypothesis testing. Results. Operating Cash Flow and Leverage have a positive effect and have insignificant effect on stock return. Conclusion. Based on the research findings, it is advisable for companies to manage operational expenses as efficiently as possible, pay attention to debt usage, and maintain their financial performance.